Sosialisasi dan Pengembangan Olahraga Cricket Siswa SMAN 1 Gowa - Karim, Achmad; Irfan; Tri Angriawan; Andi Irwandi; Muhammad Hasbillah (MAMMIRI: JURNAL PENGABDIAN MASYARAKAT, 2025)
Cricket is a sport that has a long history and is popular in many countries, but in Indonesia, this sport is still relatively new and less well-known. The socialization and development of cricket in Indonesia has its own challenges, considering the relatively low level of understanding and interest in this sport. Therefore, it is important to make various efforts so that cricket can develop further, especially at the high school level. Cricket socialization is carried out through various programs, such as introducing cricket in schools, community clubs, and social media that can reach a wider audience. In addition, regional and national level competitions also need to be encouraged to increase community involvement and motivate young athletes to participate. Cricket development can also be done by increasing training facilities, training for coaches, and collaborating with international cricket associations. It is also important to utilize the influence of sports figures and the mass media to increase the popularity of cricket. With these strategic steps, it is hoped that cricket can develop rapidly in Indonesia, create quality athletes, and build a solid fan community.